Efficacy of Ultrasound-Assisted Extraction in the Isolation of Bioactive Compounds from Pomegranate Peel (Punica Granatum L.): A Comparative Study of Solvent Performance - Pranjali Chauhan; Ekta Singh Chauhan (Asian Journal of Pharmaceutical Research and Development, 2026)
The growing nutraceutical value of Punica granatum L., also known as pomegranate, has increased in its largely discarded peel due to the content of polyphenols, flavonoids, tannins, saponins, and alkaloids. In this research, it is focused on extracting bioactive compounds from thepomegranate peel using a non-destructive environmentally friendly UAE method with hydromethanol, ethanol, and aqueous solutions. Pomegranate peels were obtained locally, dried, and powdered before extraction. Results revealed that hydromethanol was the best solvent as it produced the highest number of anthocyanins (90 mg/100g), total phenolics (2.87 GAE mg/ml), flavonoids (91.24 mg/100g), saponins (1.48%), tannins (46.29 mg/g), and alkaloids (2.87 mg/g). Ethanol extracts also exhibited promising results, especially for alkaloids (12.66 mg/g). This research puts UAE in its rightful position as a superior extraction method, further emphasizing the use of pomegranate peels as an eco-friendly bioactive compound source for functional foods and nutraceuticals. It advocates the usage of agricultural by-products and zero waste to develop natural additives in food industry that may contribute to health and environmental sustainability.